(untitled) (Journal of economic and management development research, 2025)
As the trend of e-commerce sales on self-media platforms gradually emerges, the traditional fixed-point advertising mechanism has become outdated, shifting to a model where businesses commission self-media bloggers for internet advertising. Among these, the practice of comparative product promotion by self-media bloggers has become particularly prevalent. Current legal frameworks have yet to provide clear answers on whether such comparative promotional activities by self-media bloggers constitute comparative advertising or how to regulate them under the Anti-Unfair Competition Law of the People’s Republic of China. Additionally, there are overlapping contradictions in the regulation of comparative advertising between the Anti-Unfair Competition Law and the Advertising Law of the People’s Republic of China. Therefore, addressing the practical challenges in China’s legal regulation of unfair comparative advertising, this study proposes a feasible legal framework for identifying such cases to maximize the standardized development of comparative advertising on new media platforms. Ultimately, it aims to drive the thriving growth of China’s internet platform economy through institutional innovation.